Vignettes of Naga Culture: A Reading of Easterine Kire’s Sky is My Father (Literary Voice, 2023)
Long-standing taboos and conventions are a feature of Indian civilization, and they are closely related to education. Their relationship is quite complicated and has a "chicken or the egg" nature. These two allow people to express themselves. The taboos and rituals expose the people’s indigenous religious faith and vast unheard cultural heritage. The practice of these in the society plays a kind of educative purpose to nurture the newly sprung young minds and thus these taboos and conventions reshape as well as remold the society. These are prevalent in India's Northeastern tribal society. This tribal populated land is most diverse, the cultural cauldron of India. Within Northeast India, Naga life is fully submerged in the sea of taboos that includes taboo relating to birth, death, agriculture, marriage, war etc. Each and every activity of them is bound by taboo. In a nutshell, taboo acts as an authority to determine a person's course in life. It even defines their social and cultural life. The understanding of the taboos of the Naga world is the key to unlock the treasure of the Nagas’ knowledge reservoir. The researcher through the present article will try to highlight the everyday life of the Naga tribe and in addition will focus on the educative purpose of these in the society. The present paper is solely based on the Naga novel, The Sky is My Father.
Keywords: Taboos, Rituals, Tradition, Naga, North-East India